The nature of the buffer alters the effects of the chemical modification on the stability of immobilized lipases - Abellanas-Pérez, Pedro; Carballares, Diego; Rocha-Martin, J.; Fernández-Lafuente, Roberto (Process Biochemistry, 2023)
The objective of this paper was to analyze whether an interaction between the effects of the buffer nature and chemical modification on enzyme stability exists. For this, the lipase B from Candida antarctica (CALB) and the lipase from Thermomyces lanuginosus (TLL) were immobilized on octyl agarose beads and modified with picryl sulfonic acid (TNBS) and ethylenediamine via the carbodiimide route. The obtained biocatalysts were them inactivated in different buffers (2-amino-2-(hydroxymethyl)propane-1,3-diol (Tris)-HCl, N-(2-hydroxyethyl)piperazine-N′-(2-ethanesulfonic acid) (HEPES) or phosphate). A significant interaction was found between the chemical modification of the enzyme surfaces and their stabilities in these different buffers. While phosphate was the buffer where the lowest enzyme stabilities were found for both unmodified immobilized enzymes, the differences on enzyme stabilities become much smaller after some chemical modifications. In many instances, chemical modification improves enzyme stability when using a buffer and was negative when using the other one (e.g., TNBS modification of TLL was positive using Tris-HCl or negative using the other buffers, amination of CALB decreased its stability when inactivated in Tris-HCl or HEPES while it almost had no effect in phosphate). Thus, clear co-interactions of the effects on enzyme stability between chemical modification and buffer nature were established. © 2023 The Authors DC thank to Ministerio de Ciencia e Innovaci´on-Spanish Government for a FPI. This research was funded by Ministerio de Ciencia e Innovaci´on and Agencia Estatal de Investigaci´on (Spanish Government) (PID2022-136535OB-I00). We gratefully recognize Prof. ´Angel Berenguer-Murcia for his suggestions and help during the writing of this paper. Supporting Information Peer reviewed